Rebeldes antiagraristas en el distrito de Pátzcuaro. El caso de José María Guizar y Ladislao Molina - Mendoza Arroyo, Juan Manuel; Martínez Aguilar, José Manuel (El Colegio de México, A.C., 2023)
This article analyzes the participation of Pátzcuaro Mayor José María Guizar and the landowner Ladislao Molina in a rebellion against Michoacán Governor Francisco J. Múgica. The rebels opposed the land redistribution policies promoted by Múgica, but they also acted out of loyalty to President Obregón, with whom Múgica had many public disagreements. In this rebellion, Guizar and his men traversed the towns on the shores of Lake Pátzcuaro, demanding weapons, horses and forced loans, destroying communication lines and attacking train stations. The actions of Ladislao Molina were connected to this rebellion, as well as to the intimidation of the agrarian committees promoted by the governor and the murder of the agrarian leaders of Opopeo.